PENGARUH KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI DESA LERAN KECAMATAN KALITIDU KABUPATEN BOJONEGORO - Anizarul Khoiriyah; Muhammad Farid Ma’ruf (Publika, 2022)
Land and building tax is a very potential and strategic tax as a source of state revenue. Kalitidu District consists of 18 villages, of which in the realization of the Land and Building Tax (PBB) only 4 villages with a percentage of 100%. Based on the realization of PBB-P2 data in Kalitidu Subdistrict, it shows that Leran Village is the village with the lowest realization of tax receipts having a tax payment percentage of 52.27% with the realization of the principal of PBB-P2 being paid of Rp. 218,184,417 of the total assessment ceiling of Rp. IDR 199,245,301. The purpose of this study was to determine how much influence tax awareness has on taxpayer compliance in paying land and building taxes in Leran Village, Kalitidu District, Bojonegoro Regency. This study uses quantitative methods with associative research types. The data collection technique in this study used a questionnaire. The data analysis technique used is simple linear regression, tested with a significant level of is 0.05. The results of this study indicate that taxpayer awareness has significant effect on taxpayer compliance in paying land and building taxpayers in Leran Village, Kalitidu District, Bojonegoro Regency with a simple linear regression equation, namely Y = 7.080 + 0.393X. The Adjusted R Square value is 0.370. This shows that the coefficient of determination between taxpayer awareness and taxpayer compliance is 0.370 or 37%, while the remaining 63% is influenced by other factors outside this research.